The Petrified Self 10 Years After: Current Evidence for Mnemonic anosognosia - Lenzoni, Sabrina; Morris, Robin G.; Mograbi, Daniel C. (Frontiers in Psychology, 2020)
Lack of awareness about disease, its symptoms and consequences, also termed anosognosia, is a common feature of Alzheimer’s disease (AD). It has been hypothesised that memory disorder may be a key contributing factor to anosognosia, with people with AD not being able to update their personal information about performance and relying on older consolidated material about ability. This potentially outdated sense of self has been named, as a metaphor, the petrified self. In the current review, evidence from the past ten years in relation to this concept is critically appraised. In particular, focus is given to empirical evidence produced on anterograde memory deficits about performance, the profile of autobiographical retrograde memory loss and the role of frontal lobes in anosognosia in AD. Finally, wider consequences of this metaphor for the understanding of selfhood in dementia are discussed.